MicroRNAs in cardiovascular ageing. (5th July 2015) - Seeger, Timon; Boon, Reinier A.
Abstract : Abstract: MicroRNAs (miRs) have emerged as potent regulators of pathways in physiological and disease contexts. This review focuses on the role of miRs in ageing of the cardiovascular system. Several miRs have been described to be regulated during ageing and some of these miRs are involved in the regulation of ageing‐related processes. We discuss the roles of miR‐34, miR‐217 and miR‐29, which are induced during ageing in the vasculature. The roles of miR‐34, miR‐29 (age‐induced) and miR‐18/19, which are decreased during ageing in the heart, are discussed as well. Furthermore, numerous miRs that play a role in diseases associated with ageing, like diabetes, atherosclerosis, hypertension, cardiac hypertrophy and atrial fibrillation, are also briefly discussed. miRs also serve as circulating biomarkers for cardiovascular ageing or ageing‐associated diseases. Finally, pharmacological modulation of ageing‐related miRs might become a promising strategy to combat cardiovascular ageing in a clinical setting.